Phytochemical Analysis of Carrot, Red Pepper, Spinach and Lettuce Cultivated at Ajiwa, Batagarawa, Lambun Sarki and Dankama Vegetable Farms, Katsina State, Nigeria - Dahiru, Sabiru; Salele, Yazid; Mathew, Twan Sale; Adam, Ansar Bilyaminu (Darul Yasin Al Sys, 2024)
Katsina state for long has been a major aggregation centre for cash crops including vegetables due to the availability of suitable land and adequacy of water supply, phytochemical analysis of vegitables cultivated at , batagarawa, lambun sarki and dankama vegetable farms were investigated, This study investigates the metabolites present in sample, the presence of tannins, flavonoids and saponins were tested. The results of the study showed the presence flavonoids, and tannins in lettuce, red pepper showed the presence only flavonoids, carrot showed the presence flavonoids, saponin and tannins, spinach showed the presence of tannin and saponin, while lettuce showed the presence Tannins, Saponins, Flavonoids. Therefore, lettuce, spinach and carrot could serve as potential source of natural antioxidants, red pepper could serve as a source of both antioxidant and anti-inflammatory.